Soybean Sudden Death Syndrome Influenced by Macronutrient Fertility on Irrigated Soybeans in a Corn/Soybean Rotation - Eric Adee; Dorivar Ruiz Diaz; C. R. Little (Kansas Agricultural Experiment Station Research Reports, 2017)
The effects of nitrogen (N), phosphorus (P), and potassium (K) fertilization on a corn/ soybean cropping sequence were evaluated from 1983 to 2016, with corn planted in odd years. There was a negative relationship between the P rate applied during the corn years and the severity of sudden death syndrome (SDS) in 2014 and 2016 soybean.
Keywords: Sudden Death Syndrome; SDS; phosphorus; P; soybeans